Flicka 2 [videorecording (DVD)] - Damian, Michael, 1962-; Sursok, Tammin, 1983-; Warburton, Patrick; Black, Clint; O'Hara, Mary (20th Century Fox Home Entertainment, 2010)
Carrie is a big-city teenager whose life is turned upside down when she moves to a horse ranch to live with her father. Everything changes when she meets Flicka, a jet black mustang who is just as free-spirited and strong-willed as she is.